Perancangan Program Promotion Mix pada UMKM Kedai Kelontong - Wisnu Yuwono; Tresia Putri (ConCEPt - Conference on Community Engagement Project, 2021)
The purpose of this program is to design a system promotion mix at the Kong Ye Grocery Store, which is located at Jalan Sudirman, Hutan Ayu, Pulau Rupert, Riau, through social media, so that consumers increase the number of consumers and expand customers, increase revenue and provide opportunities for customers to order a product using social media. The methods used in this activity are direct observation and interviews, system design and implementation, and evaluation. This community service program will take place in August 2020-January 2021. The results of the activity show that the existence of social media and the promotion mix carried out can help increase sales, increase marketing to the wider community, make it easier for customers to shop, and save time for customers.